2009
DOI: 10.4085/1062-6050-44.1.58
|View full text |Cite
|
Sign up to set email alerts
|

Personal and Environmental Characteristics Predicting Burnout Among Certified Athletic Trainers at National Collegiate Athletic Association Institutions

Abstract: Our findings were similar to those of other studies of burnout among NCAA Division I ATs, coaches, and coach-teachers. The results also support the Cognitive-Affective Model of Athletic Burnout proposed by Smith. Finally, these results indicate new areas of concentration for burnout research and professional practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
95
2
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(105 citation statements)
references
References 17 publications
(50 reference statements)
5
95
2
3
Order By: Relevance
“…Other researchers came to a conclusion that stress and burnout might overlap and although both constructs indicate an imbalance between resources and demands at work, the consequences of burnout can be more severe than those of stress 19) . The effects of perceived stress on the relationship between adaptive and maladaptive forms of perfectionism and burnout were examined among USA college coaches and it was found that maladaptive forms of perfectionism resulted in more threatening perceptions of stress, potentially leading to the experience of burnout 34) .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Other researchers came to a conclusion that stress and burnout might overlap and although both constructs indicate an imbalance between resources and demands at work, the consequences of burnout can be more severe than those of stress 19) . The effects of perceived stress on the relationship between adaptive and maladaptive forms of perfectionism and burnout were examined among USA college coaches and it was found that maladaptive forms of perfectionism resulted in more threatening perceptions of stress, potentially leading to the experience of burnout 34) .…”
Section: Discussionmentioning
confidence: 99%
“…Golembiewski and Munzenrider 15) describe five stages in this process, while Cherniss 16) reports three and Freudenberg 17) singles out twelve. Studies 12,18) have reported that the work of a sports coach experiencing stress was unlikely and the stress level was predictive of all 3 subscales of burnout: emotional exhaustion, depersonalization and personal accomplishment 19) . The excessive workload, multiple requirements at work including maintenance health, teaching and administration, limited staffing and financial resources for the procurement of adequate support, emotional pressure of other individuals (other coaches, members of sportsmen's families), and conflicts with colleagues and administration are mentioned as fundamental sources of burnout 11) .…”
Section: Field Studymentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, burnout has been reported to affect athletic training students, 1,2 graduate assistant ATs, 3 ATs in the collegiate and secondary school settings, [4][5][6][7][8][9] and program directors. 10 Burnout is defined as a psychological state of mental weariness that often occurs when work stresses become too much for an individual to handle.…”
mentioning
confidence: 99%
“…[17][18][19][20] These factors are organizational in nature and have been linked to experiences of burnout among ATs. 7,14 The time-intensive nature of the profession coupled with the demands of the work setting 4,7,19,21 inherently provide the platform for increased susceptibility to burnout. Interestingly, however, in a recent publication, Naugle et al 9 observed that despite working more hours, male ATs reported lower levels of burnout compared with female ATs.…”
mentioning
confidence: 99%